TRANSITIVITY SYSTEM ON JOKO WIDODO’S SPEECH AT THE APEC CEO SUMMIT ON NOVEMBER 10TH, 2014, IN BEIJING, CHINA - Harwiyati, Riris; Siagiyanto, Bambang Eko (Universitas Muhammadiyah Metro, 2016)
The aims of this research are (1) to find out the transitivity process used by Joko Widodo in his speech at the APEC CEO summit November 10th, 2014, in Beijing, China, (2) to know the most found transitivity process in Joko Widodo’s speech at the APEC CEO summit November 10th, 2014, in Beijing, China. The researchers use Systematic Functional Linguistics approach and only concern on process in transitivity system analysis by Halliday. The data collecting technique is tabulation. This is a Critical Discourse Analysis (CDA), belongs to qualitative research. The research results are (1) all of transitivity processes appeared in the speech, (2) the most found transitivity process in the speech is relational process which is 30 out of 78 utterances (38.5%).